STUDI KASUS: POST PARTUM INDUKSI ATAS INDIKASI PREEKLAMSIA DAN DIABETES MELLITUS GESTASIONAL - Hanifatun Fajria, Siti; Yuliyanti, Yeni (Journal Healthcare Education, 2023)
The incidence of preeclampsy worldwide ranges from 0.51% - 38.4%. In developed countries, the incidence of preeclampsia ranges from 6%-7%. While the incidence rate in Indonesia is around 3.8- 8.5%. In Indonesia, preeclampsia causes high maternal mortality by 24%. (Ministry of Health of the Republic of Indonesia, 2015). In 2017 there were 4,940 (9.5%) cases of preeclampsia or eclampsia in DIY Province and 397 (12.3%) in Bantul Regency (Profile of DIY Provincial Health Office, 2017). The method used is descriptive with case exposure and uses a nursing process approach including assessment, formulation of nursing diagnoses, planning, implementation, and evaluation as well as documentation. This case study was conducted for three days in providing nursing care on an ongoing basis with good cooperation between nurses and patients and patients' families, as well as with other health teams. The results of the study found seven nursing diagnoses that appeared in Mrs.H. patients. which is divided into four problems are in the literature and cases and three problems are not in the literature but exist in cases. Diagnoses that arise in cases based on IDHS are, acute pain, instability of blood sugar levels, risk of bleeding, risk of infection, ineffective breastfeeding, impaired comfort, anxiety. The conclusion of the nursing care that has been carried out on Mrs. H with Post Partum induction on indications of preeclampsia and diabetes mellitus found seven nursing problems, from seven nursing diagnoses. three nursing diagnoses whose goals were achieved, namely acute pain b.d physiological injury agent, instability of blood sugar levels b.d impaired blood glucose tolerance, ineffective breastfeeding b.d instrength of milk supply. Nursing diagnoses whose goals are achieved in part are the risk of infection b.d spontaneous postpartum episiotomy wounds, impaired comfort b.d postpartum side effects, risk of spontaneous postpartum b.d bleeding, anxiety b.d effects of invasive actions.